Efektivitas Waktu Pelumuran Ekstrak Asam Belimbing Wuluh (Avverhoa Bilimbi) terhadap Penurunan Kadar Logam Berat Merkuri (Hg) pada Ikan Mujair (O.Mosambiccus) - Goma, Jean; Sulistijowati, Rieny; Suherman, Sutianto Pratama (Transbahasa, 2024)
This study aims to analyze the effectiveness of coating time with belimbing wuluh (averrhoa blimbi) extract in reducing the heavy metal mercury (Hg) levels in Mozambique tilapia (O.mossambicus). This research employed a Completely Randomized Design (CRD) method where the data were analyzed using variance analysis (ANOVA) and further tested by Duncan's multiple range test. The study was conducted using an experimental approach with two replications at three different locations: downstream (Bolangitang River), midstream (Sonuo Village), and upstream (Ollot Village). The treatments involved different coating times with averrhoa blimbi extract. The treatment levels consisted of four control levels: 5 minutes, 10 minutes, and 15 minutes. The research results demonstrated that a 15-minute coating time with averrhoa blimbi extract significantly reduced mercury levels in Mozambique tilapia in the downstream area of the Bolangitang River, with the highest reduction percentage reaching 63%. Meanwhile, the lowest reduction percentage was observed in the midstream area (Sonuo Village), with a 10-minute coating time resulting in a reduction percentage of 20.01%. Thus, the coating time of averrhoa blimbi extract was 50% effective in reducing heavy metal mercury (Hg) levels. This study contributes significantly to understanding the potential use of natural materials in addressing heavy metal pollution in freshwater ecosystems. It also highlights the relevance of utilizing local materials such as averrhoa blimbi as an alternative in conservation efforts and the protection of the environment and fisheries resources.